Transformation of the Role and Competence of Public Relations in Using Artificial Intelligence Technology - Shellie Paola Chelsie; Erna Febriani (Publikasi Indonesia, 2024)
This research aims to determine the transformation of the role and competence of the Akarsana public relations agency in using the ChatGpt application to run PR programs. This research uses qualitative descriptive analysis with a case study approach. This research was conducted at the Akarsana Public Relations Agency. Data collection techniques were carried out using interviews, observation and documentation. The results of this research show that the use of ChatGpt supports Akarsana PR to transform from conventional PR to digital PR in the era of Industrial Revolution 4.0 and Society 5.0. With ChatGpt as an innovation, PR Akarsana can make it easier to do research and copywriting. ChatGpt also helps Akarsana's PR role as a bridge between companies and institutions or society to the public. Apart from that, Akarsana's current PR competencies must also be supported by new AI-based PR competencies so that Akarsana PR can transform optimally in the era of Industrial Revolution 4.0 and Society 5.0.